Correlation of the fifth-grade elementary school students' self-evaluation with their success in the classroom - Milijana R. Vulin (University of Belgrade, Teacher Education Faculty, 2024)
The goal of this paper is to determine the degree and direction of the correlation between the self-evaluation of the fifth-grade elementary school students and their success in the classroom. The paper presents the results of the research on students' self-evaluation and their success in the classroom obtained on a sample of 208 fifth-grade elementary school students from the territory of the city of Banja Luka. An assessment scale was used for the purposes of the research and knowledge tests for the school subjects Serbian Language and Science and Social Studies were prepared. In line with the character of the research, the method of theoretical analysis and synthesis, the survey research method, and the analytical-descriptive method were applied. The results obtained using the Pearson Correlation Coefficient confirmed that students' self-evaluation is significantly related to their general success at the end of the first term of the fifth grade of elementary school, their success at the end of the first semester in the subjects Serbian Language and Science and Social Studies, and achievements on the knowledge tests for the same school subjects. The obtained results indicate the importance of introducing student self-evaluation in the educational process in the field of achieving better results at school. However, the fact that self-evaluation is not sufficiently represented in our schools is a downside of this research, indicating a need for additional study and research of student self-evaluation, followed by its systematic introduction into educational practice.